Volcanoes - Branley, Franklyn Mansfield, 1915-2002.; Simont, Marc ([New York] : HarperCollins, 1986)
Explains how volcanoes are formed and how they affect the earth when they erupt.
First published: New York : Crowell, 1985.
Keywords: Volcanoes -- Juvenile literature; Volcanoes; Volcanoes